Quiet as a nun - Fraser, Antonia, 1932- (Weidenfeld & Nicolson, 1977)
When a murder takes place in a secluded tower at Blessed Eleanor's Convent in Sussex and the victim is an old school friend, Britain's most popular TV reporter Jemima Shore finds herself in the middle of a disturbing puzzle. The dead woman, a nun, was to inherit one of the largest fortunes in Britain. [By Publisher]